COMMUNITY-DRIVEN HEALTH STRATEGIES FOR PREVENTING DISEASE OUTBREAKS AFTER THE 2004 ACEH TSUNAMI - Hendra Cipta; Muslim; Rahmad Julianto; Rosnidawati; Teuku Maulana; Ambia Nurdin; Harri Santoso; Aisy Al-Khansa (Jurnal Penelitian Progresif, 2025)
The 2004 Aceh tsunami was one of the deadliest natural disasters in modern history, creating extreme environmental conditions that were predicted to trigger major disease outbreaks. However, despite concerns from the World Health Organization (WHO) about waterborne and infectious diseases, no widespread epidemic occurred. This study explores the community-driven health strategies that contributed to disease prevention in the aftermath of the disaster. Using a qualitative exploratory approach, data were collected through in-depth interviews with community members and local leaders across three sub-districts in Banda Aceh, each representing different levels of tsunami impact. Findings reveal that traditional knowledge, religious practices, and collective community actions played a crucial role in maintaining health and sanitation under crisis conditions. Behavioral adaptations included prioritizing clean water sources, boiling drinking water, filtering water through cloth, maintaining food hygiene, ensuring adequate nutrition, and emphasizing personal hygiene and sanitation. The study also highlights barriers to healthcare access, including infrastructure damage, medical staff shortages, and psychological distress, which affected post-disaster health-seeking behaviors. Despite these challenges, community resilience and social cohesion were instrumental in mitigating public health risks. The findings suggest that integrating local knowledge, religious teachings, and structured public health interventions can enhance disaster preparedness and disease prevention strategies in future crises. These insights provide valuable lessons for policymakers, humanitarian agencies, and public health professionals in designing culturally adaptive and community-based health resilience programs for post-disaster environments.